Resolvin E1 in Follicular Fluid Acts as a Potential Biomarker and Improves Oocyte Developmental Competence by Optimizing Cumulus Cells - Zhang, Yijing; Zhu, Zhongyi; Li, He; Zhu, Mingjiang; Peng, Xiandong; Xin, Aijie; Qu, Ronggui; He, Wen; Fu, Jing; Sun, Xiaoxi (Frontiers in Endocrinology, 2020)
Metabolic profile of follicular fluid (FF) has been investigated to look for biomarkers for oocyte quality. Resolvin E1 (RvE1), a potent pro-resolving mediator, was reported to have protective action in cell function. The study aimed to examine RvE1’s predicting value for oocyte quality and to explore the cellular mechanism of RvE1 in improving oocyte competence. Metabolic profiles of 80 FF samples showed a higher level of RvE1 in group A (blastocysts scored ≥ B3BC and B3CB according to Gardner's blastocyst scoring system, N=36) than that of group B (blastocysts scored < B3BC and B3CB, N=44, P=.0018). The receiver operating characteristic (ROC) curve analysis showed that RvE1 level in FF below 8.96 pg/ml (AUC:0.75; 95%CI: 0.64 – 0.86; P=.00012) could predict poor oocyte quality with speciﬁcity of 97.22%, suggesting RvE1 as a potential biomarker to exclude inferior oocytes. Besides, the level of RvE1 was found to be significantly lower in FF than in serum (P=.029, R2 = .063, N=76) and was gradually accumulated in CCs’ culture medium during cell culture, which indicated that RvE1 came from both blood exudates and local secretion. In vitro experiment revealed RvE1’s cellular mechanism in improving oocyte quality by decreasing CCs’ cell apoptotic rate and increasing cell viability and proliferation. It is the first time that RvE1’s role in reproduction is explored. And in this article, RvE1’s value as a potential exclusive biomarker for oocyte selection and its cellular mechanisms of influencing oocytes are investigated for the first time.